Survey expectations - Mohammad Hashem Pesaran; Martin R. Weale (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper focuses on survey expectations and discusses their uses for testing and modeling of expectations. Alternative models of expectations formation are reviewed and the importance of allowing for heterogeneity of expectations is emphasized. A weak form of the rational expectations hypothesis which focuses on average expectations rather than individual expectations is advanced. Other models of expectations formation, such as the adaptive expectations hypothesis, are briefly discussed. Testable implications of rational and extrapolative models of expectations are reviewed and the importance of the loss function for the interpretation of the test results is discussed. The paper then provides an account of the various surveys of expectations, reviews alternative methods of quantifying the qualitative surveys, and discusses the use of aggregate and individual survey responses in the analysis of expectations and for forecasting.
Keywords: C53; C50; C40; C80; 330; models of expectations formation; survey data; heterogeneity; tests of rational expectations; Rationale Erwartung; Erwartungstheorie